Management of undetectable and lost parathyroid adenoma - Catalfamo, Antonina; Famà, Fausto; Pergolizzi, Francesca Pia; Bartolo, Vincenzo; Rizzo, Antonio Giacomo; Marullo, Massimo; Fabiano, Valerio; Cancellieri, Antonino; Melita, Giuseppinella; Portinari, Mattia; Donatini, Gianluca; Makay, Ozer; et al. (Annals of Thyroid; Vol 3 (January 2018): Annals of Thyroid, 2018)
The introduction of new technologies and the improvement of localization diagnostics have led to a change of strategy in the surgery of primary hyperparathyroidism (pHPT). Focused approach to a preoperatively located parathyroid adenoma and the use of intraoperative parathyroid hormone (IOPTH) determination improve the quality of the surgical procedure and reduce morbidity. Nevertheless, the success rate of approximately 95–99% in the initial intervention could not be improved by the new or further developed technologies. The parathyroid adenoma, which cannot be found intraoperatively, is still a surgical problem today. Advances in preoperative imaging and use of IOPTH levels are even more important for the approach to re-operative parathyroidectomy. Diagnosis of persistent and recurrent pHPT is dependent on the quality and duration of follow-up, as well as the availability of biochemical data in centralized repositories. The consequence are the high cost to the patient of missed or inadequate initial operation, physical effects of remaining hyperparathyroid, additional time off work, potentially invasive localization testing, reoperative surgery, increased risk of complication and expense. To reduced failure rate is essential the correct indication, timing and type of surgery, availability of intact parathyroid hormone (iPTH) assay and the improvement of preoperative localizing studies.